PERANCANGAN APLIKASI ITBU CAREER CENTER BERBASIS WEBSITE MENGGUNAKAN PHP dan MYSQL - Panji Kresna Dhamarsa; Safrizal Safrizal; Arman Syah Putra; Suyanto Suyanto (Fakultas Teknik Universitas Persada Indonesia YAI, 2019)
ITBU Career Center Web-Based Application Design Using Php and Mysql is based on Analysis, design and Implementation. At the time of the analysis several methodologies were used to collect data in the form of literature studies, interviews and observations. The results of the analysis found that students and graduates are still difficult to obtain job vacancies information, submitting job vacancy information manually by posting paper or poster job openings on campus information boards. To provide solutions to these problems is to create a Web-based ITBU Career Center Application system. With this application designed job vacancy information can be obtained easily, quickly and clear. The design uses SDLC (System development Life cycle) by making the Uml model in the form of usecase, sequence and class diagram. For implementation in the form of program coding, the User Interface is displayed. Testing is done using Black Box Keywords: ITBU Career Center, PHP, MySql